Estrategias metodológicas y didácticas, para la comprensión de la asignatura de Estudios Sociales en los estudiantes de Octavo Año - Naranjo Moreno, Génesis Monserrate (2021)
The research work entitled "Methodological and didactic strategies for the understanding of the subject of social studies in eighth grade students", aims to respond to the educational needs that presented in the subject of Social Studies, as a methodological strategy, based on identifying the attitude with which students presented to this problem. Therefore, a descriptive research applied with the participation of 27 students belonging to the eighth year of basic education of the José María Román Educational Unit, and instruments such as the interview and the survey also used, in order to obtain a first-hand description of the factors that developed around the understanding of the subject of Social Studies. As a central point we sought to propose different strategies that favor learning in the subject of Social Studies and that above all encourage critical thinking in students, and thus give a different approach to the subject, which for years has been transmitted in an incorrect way.